Opportunity cost, willingness to pay and cost benefit analysis of a community forest of Nepal - KC, Anup; Joshi, Ganesh Raj; Aryal, Suman (International Journal of Environment, 2014)
One of the major policies in response to global climate change is reduction of green house gases emission. Community forests of Nepal are acting as major sources and sink of green house gases, in spite of providing socio-economic benefits to the user groups. There is a lack of information on whether community forests address the socio-economic disparity of user groups, and how it affects opportunity cost and willingness to pay to the forest users groups. Focusing on how the socio-economic conditions of forest users affect forest management, opportunity cost and willingness to pay; and effect of carbon trading mechanism and discounting on the cost benefit ratio, this study was carried out in one CF in western Nepal. The data collection methods included carbon stock measurement, household survey, focus group discussion and key informant interview. Study has shown that most of the forest users are in medium and poor economic classes and female involvement in forest conservation and management was remarkable. Poor people had high dependency on forest product and are most likely affected in terms of opportunity cost. Rich people were willing to pay more to sustain forest ecosystem services. Benefit cost ratio measured directly with and without discounting was 3.91 and 2.97, respectively. The findings of the present study indicate that the community forests users groups are benefitted from the current state of management. DOI: http://dx.doi.org/10.3126/ije.v3i2.10522 International Journal of the Environment Vol.3(2) 2014: 108-124